Mathematics of investment : a work text - Cervillon, Carmelita C.; Aoanan, Grace O.; Lomboy, Buencamino O. (Mandaluyong City, 2003)
This worktext was prepared primarily to suit the needs of the freshman students of the College of Business Administration of De La Salle University-Dasmarinas who are taking Mathematics of Investment subject.
Keywords: Business mathematics; Investment